Characteristics of patients with major depressive disorder switching SSRI/SNRI therapy compared with those augmenting with an atypical antipsychotic in a real-world setting. (3rd August 2021) - Kern, David M.; Cepeda, M. Soledad; Castilla-Puentes, Ruby C.; Savitz, Adam; Etropolski, Mila
Abstract: Background: Following a partial response of first-line antidepressant therapy for the treatment of major depressive disorder (MDD), there is a choice to augment treatment with another agent or switch to a different antidepressant. Objective: To report the prevalence and compare the characteristics of patients switching from their initial selective serotonin reuptake inhibitor or serotonin-norepinephrine reuptake inhibitor (SSRI/SNRI) to a new SSRI/SNRI versus those augmenting SSRI/SNRI therapy with a second-generation antipsychotic (SGA). Methods: MDD patients receiving first-line SSRI/SNRI treatment were identified from a large US-based claims database during 2000–2019. Patients augmenting therapy with an SGA were compared with those who switched to a new SSRI/SNRI. The date of the treatment change was the index date. Previously diagnosed comorbid conditions, medication use and demographics were captured. Treatment patterns following the index date were also captured. Standardized differences (StdDiff) were used to quantify dissimilarities between the two groups. Results: There were 4572 SGA add-on and 24, 409 switching patients identified. SGA augmentation patients had more severe disease (diagnosed severe recurrent major depression: 24.7% vs. 9.5%, StdDiff = 0.41) and more diagnosed psychiatric conditions, including: suicidal thoughts (10.7% vs. 3.2%, StdDiff = 0.29), post-traumatic stress disorder (6.1% vs. 2.6%, StdDiff = 0.17) and alcohol abuse (5.4% vs. 2.7%, StdDiff = 0.14). SGA augmentation patients had higher rates of prior use of anxiolytics (37.4% vs. 28.2%, StdDiff = 0.20) and anticonvulsants (26.0% vs. 13.1%, StdDiff = 0.33). Conclusions: Patients adding an SGA to their SSRI/SNRI therapy appeared to have more severe depression and comorbid psychiatric profile than those switching their SSRI/SNRI. These differences are important to consider and adequately control for in any future comparative outcome research between these two groups.